Proceedings of the 2nd Advances in Business Research International Conference ABRIC2016 (Springer Singapore, 2018)
This book contains the refereed proceedings of the 2nd Advances in Business Research International Conference (ABRIC2016). Chapters in the book address the theme of Advancing Knowledge, Connecting the World, reflecting on the emerging issues in various business management fields and the interconnections of multiple disciplines for creating knowledge advancement. Papers were carefully reviewed and selected and grouped into four main themes: economic and finance, marketing and communications, management, and information technology in business. The book serves as a helpful resource for students and researchers of business management, especially in understanding issues and cases of business in emerging economies and markets.